Case report: Combination of veno-arterial extracorporeal membrane oxygenation and intra-aortic balloon pump in a young male patient with refractory cardiogenic shock due to aluminum phosphide poisoning - Dukhin, Oleg; Bala, Danila; Felker, Evgeny; Golovina, Polina; Tretyakova, Mariya; Haes, Boris; Savvinova, Polina (Frontiers in Cardiovascular Medicine, 2023)
Background Acute toxic myocardial damage may be accompanied by the development of cardiogenic shock (CS), the mortality from which is still unacceptably high. Since there is no specific antidote for many types of toxins, treatment of such patients includes various measures of hemodynamic and respiratory support. The paper presents a case of refractory CS due to possible aluminum phosphide (AP) poisoning. Case summary A 20-year-old man was admitted to the emergency department 4 days after home inhalation of AP due to complaints of nausea, vomiting, abdominal and chest pain. Over the next few hours, he rapidly developed CS, which was refractory to conservative treatment. Therefore, veno-arterial membrane oxygenation (VA-ECMO) was performed, during which hemodynamics stabilized, but later there were signs of left ventricular overload. To unload the left ventricle (LV), an intra-aortic balloon pump (IABP) was implanted, which significantly improved the patient's condition. After 6 days the patient was decannulated, and a few more days later IABP was discontinued. Subsequently, the patient was treated for sepsis due to bilateral pneumonia and acute respiratory distress syndrome and optimal medical therapy for heart failure was prescribed. The patient was discharged after 34th day of hospitalization.